Biodiversidade troglófila do Brasil (Biotroglophilebr): uma riqueza subestimada - Duarte, Marcus Vinícius da Silva Agua (Universidade Federal de São Carlos, 2023)
Subterranean or hypogeal habitats, although they have filters for colonization, can present high biodiversity, with faunistic originality and great endemism. Such biological diversity is classically categorized into Trogloxenes (those that maintain populations in the hypogeum but have to go outside with some frequency to complete their life cycle), Troglophiles (“facultative cave dwellers”), and Troglobites (restricted to subterranean habitats), sensu Schiner-Racovitza (1907). Troglophile organisms are defined as those capable of completing their life cycles in both the epigean (surface) and hypogean environments and are important because they may be potential ancestors of future troglobites and/or possible recolonizes of the epigean environment in case of population disappearance superficial. Biodiversity studies are very important to recognize threats and allow the creation and application of effective conservation policies, but they are hampered by shortfalls or deficits, mainly Linnean (richness) and Wallacean (distribution) due to impediments to accessing underground habitats and /or descriptive impediments linked to taxonomic problems and difficulties, which lead to uncertainties regarding the diversity and distribution of animals. For hypogean habitats, biodiversity studies have a strong focus on troglobites; therefore troglophiles have historically been neglected in faunal lists. Therefore, a database on troglophiles was elaborated here, carrying out a detailed survey of works that presented faunal lists of Brazilian cavities and respective categorization of the fauna and evaluating whether the shortfalls have influenced the knowledge of troglophile biodiversity. Thus, 143 described troglophile species were registered, distributed in 32 Orders and five Phyla, of which the main representatives are spiders (41 species). These species are distributed in 14 federal states and 14 biogeographical regions of the country, with the highest concentration in Minas Gerais and São Paulo, which comprise the biogeographical province of the Paraná Forest. Furthermore, it was found that there is a strong influence of both the Linnean and Wallacean shortfalls on the knowledge of Brazilian troglophiles, and a new shortfall was considered for cave studies arising from the difficulty in categorizing an organism as a troglophile, which requires an ecological-evolutionary interpretation. The database obtained will be made available for future consultations and changes on the Webpage of the Subterranean Studies Laboratory (https://www.lesbio.ufscar.br), under the name PBioTroglophileBR.
Troglophilic biodiversity from Brazil (Biotroglophilebr): an underestimated richness
Keywords: Troglófilos; Biodiversidade; Cavernas; Levantamento; Brasil; Shortfall; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES